KFeCuTe2: a new compound to study the removal of interstitial Fe in layered tellurides. Issue 11 (2nd March 2017) - Sun, Fan; Guo, Zhongnan; Liu, Ning; Lin, Kun; Wang, Da; Yuan, Wenxia
Abstract : A KFeCuTe2 single crystal has been synthesized by the self-flux method. This new compound exhibits as an antiferromagnetic Mott semiconductor. Abstract : A single crystal of a new layered telluride KFeCuTe2 has been successfully synthesized by the self-flux method, which is formed by intercalating K in the parent telluride Fe1+ x CuTe2 . This new compound crystallizes in the space group I 4/ mmm with the interstitial Fe in pristine Fe1+ x CuTe2 completely removed after K intercalation. X-ray photoelectron spectroscopy (XPS) shows that after intercalation, the valence of Fe switched from a mixture of +2 and +3 to the single trivalent one. The KFeCuTe2 is a Mott semiconductor ( E g = 1.06 eV) with a larger resistivity than that of Fe1+ x CuTe2 due to the absence of electron doping from interstitial Fe atoms. Most importantly, the magnetic susceptibility shows the antiferromagnetic transition in KFeCuTe2 at 60 K, instead of the spin-glass behavior in Fe1+ x CuTe2, indicating the crucial role of interstitial Fe in breaking the long-range magnetic ordering. Our work provides a new compound to study the effect of interstitial Fe on the crystal and magnetic structure in layered tellurides.